Answer:
ΔH = -2552kJ
Step-by-step explanation:
Using Hess's law, it is possible to obtain ΔH of a reaction by the sum of similar reactions, thus:
1. B2O3 (s) + 3 H2O (g) → 3 O2 (g) + B2H6 (g), ΔHoA = +2035 kJ
2. 2 B (s) + 3 H2 (g) → B2H6 (g), ΔHoB = +36 kJ
3. H2 (g) + 1/2 O2 (g) → H2O (l), ΔHoC = −285 kJ
4. H2O (l) → H2O (g), ΔHoD = +44 kJ
Subtracting of 2*(2) - 2*(1):
4 B (s) + 6 H2 (g) + 6 O2 (g) → 2 B2O3 (s) + 6 H2O (g)
ΔH' = 2*36kJ - 2*2035kJ = -3998kJ
Now, this reaction - 6*(3):
4 B (s) + 3 O2(g) + 6 H2O(l) → 2 B2O3 (s) + 6 H2O (g)
ΔH'' = -3998kJ - (6*-285kJ)
ΔH'' = -2288kJ
The last reaction - 6*(4):
4 B (s) + 3 O2(g) → 2 B2O3 (s)
ΔH = -2288kJ - 6*44kJ
ΔH = -2552kJ